Cost-Benefit Analysis and European Union Cohesion Policy: Economic Versus Financial Returns in Investment Project Appraisal. Issue 1 (30th April 2018) - Florio, Massimo; Morretta, Valentina; Willak, Witold
Abstract : This paper investigates the role of cost-benefit analysis (CBA) in the context of the European Union (EU) Cohesion Policy. After presenting the EU policy framework and the CBA guidelines adopted by the European Commission, we perform an empirical analysis drawing from a dataset of around 1000 major project applications, submitted during the period 2007–2013 by 22 European countries, and representing almost €180 billion of investment. A distinctive feature of the current CBA approach adopted by the European Commission is that applications for funding must provide a forecast of both the project's financial rate of return (FRR) and economic rate of return (ERR). While the former represents the financial profitability of the project from a private investors' perspective, the latter reveals its socio-economic benefits for the whole society. The difference between ERR and FRR mainly depends on the use of shadow prices, the inclusion of externalities and other nonmarket effects in the estimation of ERR, whilst the FRR is based on market prices. We find that, on average, the FRR is slightly negative ( -2.9 %) and the ERR is positive (16.2%). ERR and FRR are positively correlated on average with differences across sectors. We discuss these findings and suggest further research needs.